Strategic risk management : a research overview - Andersen, Torben Juul; Sax, Johanna (State of the art in business research., 2020)
Organizations face challenges in adapting their current business and operational activities to dynamic contexts. Successful companies share a common characteristic of dealing with the emergent risks and threats in responses that generate viable solutions. Strategic risk management (SRM) is a multidisciplinary and rather fractured field of study, which creates significant challenges for research. This short-form book provides an expert overview of the topic, providing insight into the theory and practice. Essential reading for strategic management researchers, the authors frame the fundamental principles, emerging challenges and responses for the future, which will also provide valuable insights for adjacent business disciplines and beyond.